2022
DOI: 10.3390/su14127516
|View full text |Cite
|
Sign up to set email alerts
|

Using Flowchart to Help Students Learn Basic Circuit Theories Quickly

Abstract: College education, especially engineering education, is facing big challenges nowadays. Somehow, the gap between quickly developed modern technology used in every field and fundamental theories may discourage some students from continuing their studies in an engineering field. Most fundamental theories are taught in introductory courses in every field and are based on math, which is hard and tedious work to some students. Helping students to build a solid foundation of basic theories in engineering education n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The individual views of the participants (e.g., views of Samuel and Sabrina, see Table ) also revealed that the flowchart improved their understanding and problem-solving abilities about the topic. Similarly, the effect of the flowchart on problem-solving is mentioned in the existing literature. It seems that the FC-FLT had an enduring impact on their problem-solving abilities related to the First Law of Thermodynamics, since almost all of the participants performed better compared to the first time point without the flowchart.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The individual views of the participants (e.g., views of Samuel and Sabrina, see Table ) also revealed that the flowchart improved their understanding and problem-solving abilities about the topic. Similarly, the effect of the flowchart on problem-solving is mentioned in the existing literature. It seems that the FC-FLT had an enduring impact on their problem-solving abilities related to the First Law of Thermodynamics, since almost all of the participants performed better compared to the first time point without the flowchart.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, they mentioned that this system was also effective for students with a lower level of prior knowledge. Considering the above-mentioned studies together, it can be said that a flowchart can be a guide for students, showing them how solve the problems step by step, 31 since it helps students categorize the problems in major categories and subcategories.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The flowchart developed in this study has been shown to be an effective material for determining the isomeric relationships between pairs of organic compounds. Considering that flowcharts have explanatory, reminding, and guiding features, ,,, it can be said that students can benefit from the FCI as a supporting tool while studying. It can also help students make connections between isomerism concepts in different chapters of organic chemistry books and see various isomerism concepts holistically.…”
Section: Discussionmentioning
confidence: 99%
“…15 Flowcharts, as a type of advanced organizer, are sequential and explanatory diagrams that present the steps in any process from beginning to end, using boxes with flow arrows. 16 Flowcharts can also be used to show students how to solve a problem step by step, 17 as well as to help them remember sets of rules and identify sets of concept relationships until they become automatic. 18 There are various examples of the use of flowcharts in chemistry, such as point group classification, 19,20 naming inorganic compounds, 18,21 and problem-solving on the first law of thermodynamics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation